Pengembangan Kapasitas UKM Produk Sepatu dan Tas Kulit di Malang untuk Tembus Pasar Luar Negeri - Istutik Istutik (Indonesian Journal of Cultural and Community Development, 2018)
This program aims is to increase the capacity of craftsmen who are economically productive micro-groups. This community problems are lack of ability to manage production schedules, lack of ability to determine product prices, lack of ability to market products that rely solely on reseller buyers, and limited production capacity. The method of implementing activities to solve community problems is to provide various training, then proceed with mentoring. Sewing machine equipment assistance is provided to increase production capacity. The specific target of this program is to improve production management capabilities, determination of selling prices, marketing and soft skills of craftsmen. The impact of program implementation is increased production capacity, increased sales and income turnover, increased partner communication skills, diversity of marketing media, and community success in penetrating foreign markets.